Fahr´s Syndrome; Pseudohypoparathyroidism Type Ib Masquerading as Epileptic Seizures - Kutilek, S.; Plasilova, I.; Talabova, M.; Senkerikova, M.; Solarova, P.; Rondzikova, E.; Stefackova, S. (Kathmandu University Medical Journal, 2022)
Hypocalcaemia of various origin can be manifested by paresthesia, muscle cramps, muscle weakness, syncope, convulsions and even severe psychomotor retardation. Such symptoms can be initially considered as signs of epilepsy. We present a 12-year old boy with partial seizures and basal ganglia calcifications, initially diagnosed as having Fahr´s disease and epilepsy, where severe hypocalcaemia, due to genetically confirmed pseudohypoparathyroidism type Ib was the underlying cause. Excellent clinical improvement was observed after calcium and vitamin D therapy. The basal ganglia calcifications were secondary due to chronic hypocalcaemia, therefore the appropriate diagnosis was pseudohypoparathyroidism type Ib with Fahr´s syndrome, but not Fahr´s disease. In conclusion, the serum evaluation of minerals, especially calcium and phosphate, should be performed in all patients with convulsions, cramps and psychomotor retardation. This is essential in arriving at a proper diagnosis and early initiation of appropriate treatment.